Hubungan Tekanan Darah Terkontrol dan Tidak Terkontrol terhadap Kadar High Density Lipoprotein Pasien Hipertensi - Abi Surya Mandala; Firhat Esfandiari; Anton K.N (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Hypertension is a non-communicable disease (PTM) which is a very serious health problem both in the World and in Indonesia. Deaths of hypertension in the World are around 8 million every year, in Southeast Asia around 1.5 million. Increased blood pressure or hypertension is often followed by metabolic changes such as impaired glucose tolerance, hyperinsulinemia, hyperlipidemia, obesity, humeral changes such as the increased activity of renin, plasma, catecholamines, aldosterone, and followed by hemodynamic changes such as left ventricular hypertrophy, and impaired diastolic function. One contributing factor is a low level of High-Density Lipoprotein (HDL). From the subjects of 25 hypertension patients and 25 normal people, the average HDL profile of individuals with hypertension is lower with a significant difference between HDL profiles of hypertension individuals on normal individuals. Purpose: To find out the correlation between controlled and uncontrolled blood pressure with High-Density Lipoprotein (HDL) levels in hypertension patients at the K.Hakkiyah Central Lampung family doctor clinic in 2018. Methods: This study uses an analytical research method with a cross-sectional approach, which is by collecting data one at a time. Data will be processed and analyzed with a computer using SPSS for Windows version 20.0 program. Results: Based on the Spearman analysis, there is no correlation with the value of r = 0.118 and the value of p = 0.487 (p> 0.05). Conclusion: There is no correlation between controlled and uncontrolled blood pressure with high density lipoprotein (HDL) levels